Analisis Perubahan Struktur Ekonomi dan Tenaga Kerja di Kabupaten Badung - Priyasmini, Ni Made; Budiana, Dewa Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 11, November 2016 (pp. 1168 - 1346), 2016)
This research aimed to analyze changes in the economic structure of the Badung regency in 2005-2009 and 2009-2013 views of the GDP and employment. Data collected through the documents contained in the BPS Bali.Metode analysis used in this research is the analysis of the Shift Share (SS) and  Location Quoetient (LQ). The results of the analysis of the GDP in 2005-2009 SS indicates the transport sector accounted for 1,57 percent. In terms of employment sectors that contributed the most is the PHR sector amounted to 34,93 percent. The results of the SS GDP period 2009-2013 the transport sector accounted for 26,53 percent while for employment accounted for 30.84 percent. In the years 2005-2009 the GDP LQ analysis showed the transport sector into a sector basis LQ has an average of 2,35, in terms of employment the sector into a sector basis and have an average value of LQ most is the financial sector, real estate and business services namely 1,54. Period 2009-2013 the sector is still the dominant sector. Where LQ PDRB years 2009-2013 the transport sector has an average value LQ by 2,41 while for the financial sector, real estate and business services have an average LQ of 1,52.
Keywords: economic structure, shift share (SS), location quoetient (LQ)